Implementation of FSN Analysis and Periodic Review System for Inventory Management Improvement in Spare Parts Warehouse - Leo Rama Kristiana; Gisti Ayu Pratiwi; Putu Giri Artha Kusuma; Grass Aditya Pringgodani; Irza Farhand; Theresia Jeremia Purba (SITEKNIK: Sistem Informasi, Teknik dan Teknologi Terapan, 2026)
Effective inventory management is essential for maintaining spare parts availability and ensuring high service levels in the automotive industry. PT IAMI, particularly the PSM Dept. and PC Dept. Bekasi, identified inventory management issues at its Medan Depot as a pilot project for inventory improvement. The depot initially achieved a fill rate of only 60%, below the company’s target of 70%, due to the absence of standardized spare parts classification, review period policies, replenishment planning, and an integrated monitoring system. To address these issues, a community service program was conducted by Telkom University through technical assistance in developing an inventory management framework. The program integrated Fast-Slow-Non Moving (FSN) Analysis, the Periodic Review System (R,s), and a dashboard-based inventory monitoring system using Microsoft Excel. The implementation stages included field observation, focus group discussion, operational data analysis, spare parts classification, inventory parameter calculation, dashboard development, and validation with the partner. The results showed that the proposed inventory policy improved the fill rate from 60% to 99%, exceeding the company target. In addition, the dashboard improved inventory visibility by displaying stock status, fill rate, safety stock, reorder warnings, and other operational indicators.